Piezoelectric Chemosensors and Biosensors in Medical Diagnostics - Pohanka, Miroslav (Biosensors, 2025)
This article explores the development and application of innovative piezoelectric sensors in point-of-care diagnostics. It highlights the significance of bedside tests, such as lateral flow and electrochemical tests, in providing rapid and accurate results directly at the patient's location. This paper delves into the principles of piezoelectric assays, emphasizing their ability to detect disease-related biomarkers through mechanical stress-induced electrical signals. Various applications of piezoelectric chemosensors and biosensors are discussed, including their use in the detection of cancer biomarkers, pathogens, and other health-related analytes. This article also addresses the integration of piezoelectric materials with advanced sensing technologies to improve diagnostic accuracy and efficiency, offering a comprehensive overview of current advances and future directions in medical diagnostics.
Keywords: Electrochemical Techniques; biologické markery; bedside test; Biomarkers; clinical biochemistry; lidé; QCM; diabetes; Biosensing Techniques; blood; quartz crystal microbalance; piezoelectric cantilever beam; elektrochemické techniky; Point-of-Care Systems; biosenzitivní techniky; vyšetření u lůžka; inflammation; marker; point-of-care test; Humans